2013
DOI: 10.1039/c3cp50991e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Li+ dynamics of Sb-doped Li7La3Zr2O12 fast lithium ion conductors

Abstract: Antimony-doped lithium stuffed garnets Li(7-x)La3Zr(2-x)Sb(x)O12 (x = 0.2-1.0) prepared using a conventional solid state reaction method are characterized using Powder X-ray Diffraction (PXRD), Scanning Electron Microscopy (SEM), Energy Dispersive Analysis by X-ray (EDAX), AC Impedance spectroscopy, Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) and Raman spectroscopic techniques. PXRD confirms the formation of a garnet-like structure with cubic symmetry for the entire selected compositional range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 38 publications
2
75
0
1
Order By: Relevance
“…[16][17][18][19] The prevailing assumption has been that the Li content (i.e., carrier concentration) is responsible for the high Li-ion conductivity. [ 10,16,19 ] However, Ohta et al noted that when the carrier concentration is calculated based on this assumption, it can be found that the conductivity is not increasing linearly with the carrier concentration. Since the carrier concentration (assuming all the ions participate in conduction) does (5 of 9) 1500096 wileyonlinelibrary.com not change enough to explain the increase in conductivity, it was thought that changes to the mobility caused by the dopant must, therefore, be controlling the conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] The prevailing assumption has been that the Li content (i.e., carrier concentration) is responsible for the high Li-ion conductivity. [ 10,16,19 ] However, Ohta et al noted that when the carrier concentration is calculated based on this assumption, it can be found that the conductivity is not increasing linearly with the carrier concentration. Since the carrier concentration (assuming all the ions participate in conduction) does (5 of 9) 1500096 wileyonlinelibrary.com not change enough to explain the increase in conductivity, it was thought that changes to the mobility caused by the dopant must, therefore, be controlling the conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23,28 ] Li conducting garnets have been analyzed using the same assumption that all the Li-ions contribute to the conductivity. [ 10,16,19 ] However, recent experimental evidence shows that this assumption is not valid for the garnet family of materials. [ 29 ] Thus, in order to clarify what is the effective carrier concentration in the garnet family of ionic conductors, a compositional series of cubic stabilized garnet ionic Li ion conductors, Li 7− x La 3 Zr 2− x Ta x O 12 (x = 0.5, 0.75, and 1.5), was synthesized and the relationship between site occupancy and effective carrier concentration was determined.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Optimization efforts have focused on obtaining the cubic phase by promoting disorder across the Li sublattice; dopant incorporation is typically employed, targeting the framework cation sites (i.e., La and Zr). Some notable improvements were reported for Te-doped LLZrO (1.02 × 10 −3 S/cm), 15 Tadoped LLZrO (1.0 × 10 −3 S/cm), 16−19 Nb-doped LLZrO (8.0 × 10 −4 S/cm), 20 Sb-doped LLZrO (7.7 × 10 −4 S/cm), 21 and Sr-doped LLZrO (5.0 × 10 −4 S/cm). 22 Simultaneous substitution was also explored in the series Li 7+x−y (La 3−x A x )-(Zr 2−y Nb y )O 12 (where A is an alkali earth metal) and has shown that an optimum lattice parameter at a constant lithium content of 6.5 per formula unit (p.f.u.)…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this decade, the garnet-related type Li 7 La 3 Zr 2 O 12 , which was reported by R. Murugan et al for first time, 1) has been studied from view points of the chemical stability, the conductive properties and the crystal structure in detail. In order to increase the Li-ion conductivity of the garnet-type Li 7 La 3 Zr 2 O 12 , a large number of studies on the chemical substitution using various cation species has been reported.…”
Section: Introductionmentioning
confidence: 99%